A bone adhesive enhances osteoporotic fracture repair by regulating bone homeostasis - Shenghui Su; Jiajun Xie; Jian Gao; Shencai Liu; Xieping Dong; Jianwei Li; Zhong Feng Gao; Keyuan Chen; Weilu Liu (NPG Asia Materials)
Abstract Patients suffering from osteoporotic fractures often require effective fixation and subsequent bone repair. However, the currently available materials are functionally limited and often fail to improve outcomes in this patient population. In this study, we developed orthopedic adhesives doped with romosozumab-loaded mesoporous bioactive glass nanoparticles to aid in osteoporotic fracture fixation and restore dysregulated bone homeostasis. These adhesives were designed to promote osteoblast formation while simultaneously inhibiting osteoclastic bone-resorbing activity, thus working synergistically to promote the healing of osteoporotic fractures. Orthopedic adhesives exhibit injectability, reversible adhesiveness, and malleability, enhancing their adaptability to complex clinical scenarios. Furthermore, the release of romosozumab from mesoporous bioactive glass nanoparticles accelerated osteogenesis and inhibited osteoclastogenesis, delaying the bone resorption process. This dual action contributes to the regulation of bone regeneration and remodeling. Notably, our orthopedic adhesive could restore the disrupted bone homeostasis associated with osteoporotic fractures.